OCEAN CURRENTS ENERGY FOR ELECTRICITY GENERATION AND ITS POTENTIAL IN EAST JAVA WATER, INDONESIA - Nurin Hidayati; Muhammad Mahmudi; Dhira Kurniawan Saputra; Muhammad Musa; Hery Setiawan Purnawali (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2016)
Electrical energy is one of the vital needs of the coastal communities, especially in coastal areas that are not affordable electricity network. To meet these needs energy diversification efforts are undertaken, such as the utilization of the energy potential of ocean currents. The aim of this study was to determine the seabed morphology and properties of hydro-oceanography as a reference the exact location in the utilization of the energy of ocean currents. Location of research in the territorial waters of East Java. Research methods such as measurement of currents, tidal observation, observation of meteorological parameters and conditions of the seabed morphology and the coastal area of research. The study was conducted to estimate the potential energy of ocean currents are spatially and temporally by utilizing a hydrodynamic model simulation results and the results of current data measurement in the field, and convert them into power unit. Which will ultimately produced maps of potential energy from ocean currents of East Java waters territory. In comparison, there are several advantages of ocean current energy utilization compared to other energy generation, such as the production of electricity generated by ocean currents each year tend to be stable and more environmentally friendly because without using fuel. Potential sites for power plants in East Java waters of the ocean currents are respectively Madura Strait Region, Southern Water of East Java, and Bali Strait water.Keywords: Ocean Currents, Energy, East Java